1989
DOI: 10.2466/pr0.1989.65.1.83
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and Illness Image: An Analysis of Diabetic Early-Adolescents' Self-Perception through the Draw-a-Person Test

Abstract: To study the self-projective representations expressed by diabetic children, aged between 10 and 15 yr., and to compare these with representations of a control group the Draw-a-person test associated with those for subsequent Draw-a-sick-person were administered to 23 children regularly checked by an Antidiabetic Centre. The diabetic subjects drew an image of "sick person" having projective elements with a regressive value and denoting a refuge in the past, together with depressive signs of retiring into thems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Although these hypotheses are to be considered with caution, given the notable limitations of the analysis of drawings on the basis of single items (Flanagan and Motta, 2007), they are in line with the studies which show that drawings by children with type 1 diabetes or other chronic illnesses have the presence of distinctive aspects linked to the illnesses. The drawings of children with type 1 diabetes are described as being characterised by elements which testify differences in awareness and perception of the body when compared to controls (Eiser et al, 1984), as showing problems of adaptation and a sense of difference (Nuvoli et al, 1989) or as a sign of general emotional difficulty (Kortesluoma et al, 2008). Our data, in other words, indicating greater accuracy in body size perception and the presence of distinctive elements in human figure drawings, suggest the existence of aspects of body image which characterise children with type 1 diabetes and distinguish them from healthy children.…”
Section: Discussionmentioning
confidence: 99%
“…Although these hypotheses are to be considered with caution, given the notable limitations of the analysis of drawings on the basis of single items (Flanagan and Motta, 2007), they are in line with the studies which show that drawings by children with type 1 diabetes or other chronic illnesses have the presence of distinctive aspects linked to the illnesses. The drawings of children with type 1 diabetes are described as being characterised by elements which testify differences in awareness and perception of the body when compared to controls (Eiser et al, 1984), as showing problems of adaptation and a sense of difference (Nuvoli et al, 1989) or as a sign of general emotional difficulty (Kortesluoma et al, 2008). Our data, in other words, indicating greater accuracy in body size perception and the presence of distinctive elements in human figure drawings, suggest the existence of aspects of body image which characterise children with type 1 diabetes and distinguish them from healthy children.…”
Section: Discussionmentioning
confidence: 99%
“…The 3-year age advancement was purposeful, reflecting likely advancement to the next academic level, representing developmental maturation (15). Youth were observed without comment and then interviewed using a predetermined script in a structured format (16). The structured format was selected for consistency in the interview process to improve interrater reliability (17).…”
Section: Methodsmentioning
confidence: 99%
“…Some studies have indicated that diabetes has negative effects on self-concept (Nuvoli, Maioli, Ferrari, Pala and Chiaretti, 1989;Sullivan, 1979;Swift, Seidman and Stein, 1967). Muldoon (1978) asserts that since significant others treat diabetic children differently, they treat themselves differently and find it difficult to feel a sense of continuity and similarity with others.…”
Section: Psychological Characteristicsmentioning
confidence: 99%